Asuhan Kebidanan Berkesinambungan Ny.C 32Th di PMB Nur Ika Rahayu Kota Batam - Farah Zahidah Imtinan; Siti Husaidah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The goal of continuous midwifery care is to use the SOAP documentation technique to provide comprehensive care to pregnant women up to birth control according to care standards. From May 2 - July 14, 2025, Mrs.C, G2P1A0, 32 years old received continuous midwifery care from pregnancy until get contraception methods, starting at 34 weeks of gestation. The mother complained of back pain during prenatal check-ups. The labor process went smoothly. With the assistance of a midwife, the baby was born on June 10, 2025. Birth weight: 3000 grams; length: 50 cm; head circumference: 34 cm; chest circumference: 33 cm; received Hb0 vaccine two hours after birth, eye ointment, and vitamin K shortly thereafter. The baby did not experience any problems or complaints during the first visit. Mrs. C received four visits during the postpartum period. The mother did not feel anything during the first visit up to the following visits. She continued to breastfeed exclusively, and her vital signs and fundal height returned to normal. The mother used a three-month injectable contraceptive so as not to interfere with the exclusive breastfeeding program. Mrs.C has received continuous midwifery care during pregnancy and contraceptive use, and her health is normal. It is expected that the midwife will be able to provide continuous midwifery care so that in the event of an emergency, it can be immediately identified and promptly handled.